Activities for Residents of Dutch Nursing Homes during the COVID-19 Pandemic: A Qualitative Study - Marlon M. P. Smeitink (International Journal of Environmental Research and Public Health, 2022)
To protect nursing home residents from getting infected with COVID-19, several measures have been imposed. The aim of this study was to describe the impact of these measures on activities for Dutch nursing home residents, the conditions under which the activities could take place, and the considerations when making decisions about the (dis)continuation of activities. The study consisted of the data of the qualitative MINUTES-study. Textual units derived from documentation of an outbreak team (OT) meetings on activities, well-being, informal caregivers, and volunteers from 39 long-term care organizations were re-analyzed using a content analysis. The results shows that OTs more often discussed restarting and continuing activities than stopping activities during the COVID-19 pandemic. There were differences between time periods, but activities never completely stopped according to the minutes. Activities were offered in an adapted way, often under certain conditions, such as organizing activities at other locations (e.g., outside), with limited group size, and following specific guidelines. The main focus of the considerations made were the ability to adhere to the guidelines, the well-being of residents, ensuring safety, and balancing benefits versus risks given vaccination availability and coverage. Overall, the study showed that organizing activities for nursing home residents despite COVID-19 measures is possible.